A large high-efficiency multi-layered Micromegas thermal neutron detector. (8th September 2017) - Tsiledakis, G.; Delbart, A.; Desforge, D.; Giomataris, I.; Menelle, A.; Papaevangelou, T.
Abstract: Due to the so-called 3 He shortage crisis, many detection techniques used nowadays for thermal neutrons are based on alternative converters. Thin films of 10 B or 10 B 4 C are used to convert neutrons into ionizing particles which are subsequently detected in gas proportional counters, but only for small or medium sensitive areas so far. The micro-pattern gaseous detector Micromegas has been developed for several years in Saclay and is used in a wide variety of neutron experiments combining high accuracy, high rate capability, excellent timing properties and robustness. We propose here a large high-efficiency Micromegas-based neutron detector with several 10 B 4 C thin layers mounted inside the gas volume for thermal neutron detection. The principle and the fabrication of a single detector unit prototype with overall dimension of ∼ 15 × 15 cm 2 and a flexibility of modifying the number of layers of 10 B 4 C neutron converters are described and simulated results are reported, demonstrating that typically five 10 B 4 C layers of 1–2 μ m thickness can lead to a detection efficiency of 20–40% for thermal neutrons and a spatial resolution of sub-mm. The design is well adapted to large sizes making possible the construction of a mosaic of several such detector units with a large area coverage and a high detection efficiency, showing the good potential of this novel technique.